Role of GnRH Isoforms in Paracrine/Autocrine Control of Zebrafish (Danio rerio) Spermatogenesis - Fallah, Hamideh P.; Rodrigues, Maira S. [UNESP]; Corchuelo, Sheryll [UNESP]; Nobrega, Rafael H. [UNESP]; Habibi, Hamid R. (Endocrine Soc, 2020)
It is well established that hypothalamic GnRH (gonadotropin-releasing hormone) is one of the key peptides involved in the neuroendocrine control of testicular development and spermatogenesis. However, the role of GnRH as a paracrine regulator of testicular function has not been fully investigated. The present study demonstrates the presence of GnRH and its receptors in the zebrafish (Danio rerio) testis, and provides information on direct action of native GnRH isoforms (GnRH2 and GnRH3) on different stages of spermatogenesis in this model. Both GnRH2 and GnRH3 stimulated basal spermatogenesis by increasing numbers of type A(und) spermatogonia, spermatozoa, and testosterone release, and in this study GnRH2 exerted higher relative activity than GnRH3. Next, we evaluated the effects of GnRH isoforms on human chorionic gonadotropin (hCG)- and follicle-stimulating hormone (Fsh)-induced spermatogenesis. The 2 GnRH isoforms were found to have different effects on Fsh- and hCG-induced response depending on the stage of spermatogenesis and concentration of the peptides. The results provide strong support for the hypothesis that locally produced GnRH2 and GnRH3 are important components of the complex multifactorial system that regulates testicular germinal cell development and function in adult zebrafish.
Keywords: gonadotropin-releasing hormone (GnRH); chicken GnRH-II (GnRH2); salmon GnRH (GnRH3); human chorionic gonadotropin (hCG); follicle-stimulating hormone (Fsh); zebrafish spermatogenesis